A natural bioactive feed additive alters expression of genes involved in inflammation in whole blood of healthy Angus heifers. Issue 4 (May 2020) - Armstrong, Shelby A; McLean, Derek J; Bionaz, Massimo; Bobe, Gerd
A greater demand for food animal production without antibiotics has created the common practice of feeding food animals dietary immunomodulatory feed additives (IFA) throughout their life cycle. However, little is known about the impact of IFA on cytokine and chemokine signaling in non-stressed, non-pathogen-challenged food animals during the early feeding period. We evaluated the expression of 82 genes related to cytokine and chemokine signaling in the whole blood of growing Angus heifers to determine the effect of IFA supplementation on cytokine and chemokine signaling during the first 28 d of feeding. One gene ( CCL1 ) was significantly up-regulated and 14 genes (17%) were significantly down-regulated by IFA feeding during the entire early feeding period including 5 of 21 (24%) evaluated chemokine and IL receptors (CCR1, CCR2, IL1R1, IL10RA, IL10RB ). These data when taken together suggest providing an IFA in the diet of growing beef cattle during the early feeding period may suppress the inflammatory response through cytokine–cytokine receptor signaling.